Blended Learning Model to Improve Learning Independence in Students of Elementary School Teacher Education - Sukatin Sukatin; Mahdeyeni Mahdeyeni; Aniyanti Ginanjar; Nurul Fatonah; Endang Meiliani; Pahmi Pahmi (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purpose of this study is to find out how the application of the blended learning model to the learning independence of PGSD students. The approach used in this research is descriptive quantitative with data analysis using percentages. The research subjects were students of the 2020 Garut University PGSD Study Program as many as 41 respondents. In this study, a sample was taken using a purposive sampling technique with a population of PGSD students as a whole. The results showed that student learning independence was successfully improved using the blended learning model, which was above 50 percent and included indicators of confidence, initiative, and motivation. Meanwhile, student responses related to the use of the blended learning model have an average of 61.9 percent, which is a positive response. So, it can be said that the blended learning model can increase the learning independence of PGSD students.